Assessment of microtensile bond strength of different caries removal techniques with ICDAS scores - KANAR, ÖZLEM; TAĞTEKİN, DİLEK; KORKUT, BORA (My University, 2023)
This study aimed to evaluate the effect of different caries removal techniques and ICDAS scoring to microtensile bond strength (µTBS). Fourty-eight human molars assessed clinically and having scores of 0, 3, 4 and 5 based on Internaonal Caries Detecon and Assessment System (ICDAS) criteria were inspected. Group ICDAS 0 taken as control for microtensile test. Each group was divided into 4 groups as 1 complete caries removal (CCR) and 3 selecve caries removal (SCR) methods: these are stainlesssteel round bur (SSRB), ceramic round bur (CRB), tungsten carbide round bur (TCRB) & bioacve glass powder (BAG), TCRB & 29 µm Al2O3, respecvely (n=3). Following the restoraon, five 1 mm2 sckshaped specimens were prepared from each tooth with a slow-speed diamond trim blade (Isomet, Buehler, Lake Bluff, Illinois, USA) (n = 15). Specimens were subjected to µTBS stress at a crosshead speed of 0.5 mm/min (Bisco, Schaumburg, IL, USA). Generalized linear model and Tukey's test were used for stascal analysis (p ≤ 0.05). Caries removal technique was considered significant between all groups (p≤0.001). The mean of µTBS ranged from 14.2 megapascal (MPa) (%95CI: [12.1-20.5]) to 26.4 (%95 CI:[11.7- 28.4]). The mean±standard deviaon of µTBS were obtained as 19.5±3.9 MPa for SSRB, 16.4±3.3 MPa for CRB, 15.0±3.0 MPa for the TCRB&BAG group and 25.1±2.1 MPa for the TCRB&Al2O3 groups, respecvely. ICDAS scores showed stascally significant effect for µTBS values (p≤0.001). Similar µTBS values were obtained for ICDAS 0 (20.1±4.9) and ICDAS 3 (19.9±4.6) scores, which are higher than ICDAS 4 (17.9±4.4) and ICDAS 5 (18.2±5.6) scores. In conclusion, the µTBS for sound denne were less affected by the caries removal technique. Within the limitaons of this study, it can be concluded that the air-abrasion with 29 µm Al2O3 may be preferred to increase µTBS for deep carious lesions.